PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PROGRAM KELOMPOK USAHA BERSAMA (KUBE) TAHUN 2023 (Studi Kasus Di Desa Tawangsari Kecamatan Garum): - , Dwi Wahyu Ningsih; Mochammad Alexander Mujiburrohman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Empowerment of the poor is one of the main focuses in poverty reduction efforts in Indonesia. The Joint Business Group (KUBE) program launched by the Ministry of Social Affairs of the Republic of Indonesia aims to empower underprivileged families through the provision of social assistance in the form of Productive Economic Enterprises (UEP), with the hope of increasing their income and social welfare. This study aims to describe community empowerment through the KUBE Program in Tawangsari Village, Garum Sub-district, Blitar District. Using a descriptive qualitative approach, this study evaluates the success of empowerment activities as well as the role of KUBE in improving the welfare of the poor. The results showed that the implementation of KUBE in Tawangsari Village involved three main stages: awareness raising, capacity building, and empowerment. Supporting factors such as government regulations and a monitoring system contributed positively to the success of the program. However, this study also found that the limited quality of funds received by the groups was a major obstacle in the implementation of the program. Therefore, this study recommends strengthening partnerships and more systematic monitoring as solutions to overcome these obstacles.